Comparison of Au–Ce and Au–Cu interaction over Au/CeO2–CuO catalysts for preferential CO oxidation. Issue 2 (10th December 2018) - Jing, Guojuan; Zhang, Lu; Ma, Yurong; Wu, Jinfang; Wang, Qi; Wu, Guoqing; Yan, Lihui; Zeng, Shanghong
Abstract : Au decelerates reduction of copper species, while it improves ceria reduction. Abstract : Understanding how the content of noble metal alters the catalytic performance of the corresponding catalysts is vital for the construction of active catalysts. This work investigates Au/CeO2 –CuO catalysts with different Au contents for preferential CO oxidation (CO-PROX), aiming to reveal the origin of the high catalytic performance. A series of Au/CeO2 –CuO catalysts are prepared by the co-precipitation method. The studies reveal that Au nanoparticles, which are located at the surface of CeO2 clusters, could decrease the activation energy of the CeO2 –CuO catalyst at low temperature. Furthermore, the introduction of Au species decelerates the reduction of copper species, leading to a wider temperature window of complete CO conversion. Meanwhile, the Au species improves the reduction of ceria which facilitates the catalytic activity. The catalytic tests show that Au/CeO2 –CuO catalysts display better catalytic performance than the one without Au nanoparticles and it increases with increasing content of Au species, which originates from the strong synergistic interaction between Au and CeO2 –CuO species. This synergistic effect is further verified by DFT calculations. The results show that Au species tend to locate on the CeO2 surface rather than the CuO surface. Besides, the increase of the Au amount leads to the enhancement of CO adsorption energy on Au/CeO2, which is conducive to the improvement of catalytic activity for CO oxidation.